Estimating the Return on Education: Evidence from Indonesian Survey Data - Muhammad Ciro Danuza; Alfa Farah (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
In the Mincerian framework, the return on education shows how an incremental increase in earnings is related to an increase in schooling. Employing a survey data, the Indonesia Family Life Survey Wave 5(IFLS 5), this study attempts to estimate the return on education in Indonesia. The baseline results show that one extra year of schooling increases future earnings by 5.7%. When parental education used as instruments, the IV estimates show a rate of 12%. These results are consistent with the Mincerian framework and the previous studies.